Semaphorin 7A modulates cytokine-induced memory-like responses by human natural killer cells - Ghofrani, Joshua (Eur J Immunol, 2019)
Cytokine-induced memory-like (CIML) NK cells are endowed with the capacity to mediate enhanced effector functions upon cytokine or activating receptor re-stimulation for several weeks following short-term pre-activation with IL-12, IL-15 and IL-18. Promising results from a first-in-human clinical trial highlighted the clinical potential of CIML NK cells as adoptive immunotherapy for patients with hematologic malignancies. However, the mechanisms underlying CIML NK cell differentiation and increased functionality remain incompletely understood. Semaphorin 7A (SEMA7A) is a potent immunomodulator expressed in activated lymphocytes and myeloid cells. In this study, we show that SEMA7A is substantially upregulated on NK cells stimulated with cytokines, and specifically marks activated NK cells with a strong potential to release IFN-γ. In particular, pre-activation of NK cells with IL-12+IL-15+IL-18 resulted in greater than 10-fold upregulation of SEMA7A and enhanced expression of the ligand for SEMA7A, integrin-β1, on CIML NK cells. Strikingly, pre-activation in the presence of antibodies targeting SEMA7A lead to significantly decreased IFN-γ production following re-stimulation. These results imply a novel mechanism by which cytokine-enhanced SEMA7A/Integrin-β1 interaction promotes CIML NK cell differentiation and maintenance of increased functionality. Our data suggest that targeting SEMA7A/Integrin-β1 signaling might provide a novel immunotherapeutic approach to potentiate antitumor activity of CIML NK cells.